La abeja no debe volar, pero vuela - Martínez, Juan Ramón (Oltreoceano - Rivista sulle migrazioni, 2021)
Rutenia es el lugar escogido para los encuentros tertulianos, de aquí parte la historia de una joven víctima de abuso sexual por un familiar, motivo suficiente para enfrascarse en el “sueño americano”. La venganza, platillo que se come frío, se consuma después de un periplo individual del personaje principal. Bees Should Not Fly, Yet Do Ruthenia is the place chosen for social gatherings and the setting for the story of sexual abuse on a young victim by a relative, which is reason enough to get caught up in the "American dream". Revenge, a dish eaten cold, is consumed after an individual journey embarked on by the main character.